Day case orthopaedic trauma surgery effectiveness: a systematic review - Buchanan, Donald; Sarhan, Islam; Hind, Jamie; Sidhu, Gur; Dekker, Andrew; Ashwood, Neil (International Journal of Research in Orthopaedics, 2023)
Day case surgery facilitates effective orthopaedic care for ambulatory trauma cases and can act as an effective pathway in times of reduced resource availability within acute hospitals. A systematic review of the available literature was performed using a narrative synthesis to look for themes underpinning day case trauma practice. A 25 papers were selected from a total of 9956 papers screened to identify those papers that considered day case trauma surgery and its impact on clinical outcome, patient satisfaction and feasibility of delivery within the UK. 9014 patients had day case trauma operations within the 25 papers identified, 86% had general anaesthesia and 14% either regional or local anaesthesia. The mean reported age was 37.5 years with a wide age range (2-83) years treating roughly similar proportions of men and women with a high satisfaction rate when recorded. All areas of the upper limb were operated on apart from the scapula the commonest being the wrist. In the lower limb surgery was undertaken in the knee, ankle or foot with removal of foreign body or ankle fixation being the commonest procedures undertaken. Prevalence of complications at 0.0156% of cases undergoing day case surgery was seen to be lower than in a similar group of inpatient cases. resources are stretched. Day case surgery for trauma procedures within orthopaedics is safe, cost effective and well tolerated by patients. It frees up resources to facilitate treatment and should be utilised within each hospital to enable timely care.